STUDI KUALITATIF: KECEMASAN PADA PENDERITA PREEKLAMPSIA - Purwati; Alfi Noviyana (Jurnal Infokes, 2020)
The cause of preeclampsia until now has not been known with certainty, some studies say that psychological pregnancy can affect the occurrence of preeclampsia. Anxiety is one of the psychological disorders experienced by pregnant women. The purpose of this study was to determine the cause of anxiety in pregnant women who experience pre-eclampsia. qualitative research methods with a case study approach. Sampling was done by purposive sampling. Respondents consisted of 6 main respondents and 8 supporting respondents. The study was conducted in the Flambiyan Room of Goeteng Tarunadibrata Hospital, Purbalingga. The results showed that most of the age above 35 years had preeclampsia and less than 20 years also had preeclampsia. 5 respondents did not experience anxiety before knowing that their blood pressure had risen and there was an increase in blood pressure when they knew they would be referred.Conclusion anxiety in pregnant women occurs after knowing the diagnosis of preeclampsia submitted by health workers. This triggers fear in pregnant women, causing anxiety. Anxiety that occurs in pregnant women can worsen or increase blood pressure.